The Influence Of Third Party Funds And Capital Adequacy On The Financial Performance Of Banking Companies Listed On The IDX In 2018-2022 - Desti, Firli Maya; Mayliza, Riri (Management Studies and Entrepreneurship Journal (MSEJ), 2024)
Financial performance is a financial report that shows the financial condition of a company, which is used as material for the company to consider whether the company's financial condition is good or bad, so that further action can be taken and the public can assess the smooth running of the company. The purpose of this study was to determine the effect of third party funds and capital adequacy of banking companies on the financial performance of companies listed on the IDX. The analysis method used by researchers is the panel data regression analysis method and purposive sampling technique, and the data used is the financial statement data of manufacturing companies in the banking sub-sector listed on the Indonesia Stock Exchange (IDX). For the period 2018-2022 Based on hypothesis testing, the research results show that third party funds have a negative and insignificant effect on financial performance, while capital adequacy has a positive and significant effect on bank financial performance.